Concept mapping as a scaffolding technique in the teaching of EFL reading comprehension among undergarduates in China - Ta, Na (2023)
Reading is an essential skill in which it is an interactive process and a fundamental life-long learning tool, which is crucial to students’ personal and professional success. Enhancing reading skills has long been a focal point of researcher endeavors. Within this context, concept mapping emerges as a potent technique for improving learners’ reading comprehension. Employing a mixed research method, this study combines a quasi-experimental design with qualitative semi-structured interviews. 135 Chinese undergraduates from Chifeng University were recruited and randomly assigned to three groups: the full concept mapping group, the group combining concept mapping and conventional method, and the conventional method group. The full concept mapping group received instruction exclusively centered around the scaffolding technique of concept mapping. In contrast, the group combining concept mapping and conventional method engaged in conventional instruction during the while-reading phase and used concept mapping in the after-reading phase. The conventional method group underwent regular conventional reading instruction throughout the semester. Post-test results unveiled the significant superiority of the combining concept mapping with conventional method group (mean=85.42) over both the full concept mapping group (mean=80.20) and the conventional method group (mean=74.11). Delayed post-test outcomes reinforced the effectiveness of combining concept mapping with conventional method (mean=78.91) compared to full concept mapping (mean=74.51). These findings underscore the advantage of combining concept mapping with conventional method for immediate and enduring enhancements in reading comprehension. Subsequent to the quasi-experiment, semi-structured interviews were conducted with nine participants, revealing that the utilization of concept mapping stimulated the employment of reading strategies and positively influenced attitudes. Thus, this study advocates that the most efficacious approach to incorporating the concept mapping technique into English as a Foreign Language reading comprehension instruction is through its integration with conventional method. Drawing from these findings, this study contributes to theoretical insights by synthesizing various theories to elucidate the multifaceted process of EFL reading comprehension. Additionally, it provides valuable practical implications for curriculum developers, policymakers, educators and researchers, thereby enhancing the implementation and future exploration of this technique.